GENETIC DIVERSITY OF KEJOBONG GOAT BASED ON MITOCHONDRIAL DNA D-LOOP SEQUENCE - M. F. Harlistyo; S. Sutopo; E. Kurnianto (Journal of the Indonesian Tropical Animal Agriculture, 2014)
This study was aimed to find out the diversity of mtDNA D-loop at Kejobong goat. The completemtDNA D-loop sequence of 12 goat blood samples were analyzed from 4 different location inPurbalingga Regency, Central Java province, sub-districts Kejobong, Pangadegan, Bukateja, andKaligondang. The mtDNA D-loop was extracted from blood sample. DNA obtained were amplified byPCR (Polymerase Chain Reaction) method using primers (5’-tcactatcagcacccaaagc-3’) as forward and(5’-ggcattttcagtgccttgct-3’) as reverse and subsequently sequenced. After nucleotide sequencing analysisconducted, 548 bp along was obtained. Nucleotides were then aligned with Capra hircus (GenBankAccess No.: KF952601.1) and apparently there were 11 different sites on the segment of mtDNA Dloop.Five sites could be used as a specific marker to distinguish between the Capra hircus andKejobong goat, namely at the site of 317 (A-G), 403 (T-C), 434 (T-C), 537 (C-T), and 553 (A-G).Nucleotide sequence analysis also contained seven different haplotypes. It was concluded that thedistribution of the different sites showed different haplotype patterns in Kejobong goat.